2022
DOI: 10.36150/2499-6564-n357
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided cognitive training in patients with neurocognitive vascular impairment: effects on cognition, depression and behavior

Abstract: How to cite this article: Vaia S, Iavarone A, Moschiano F, et al. Computer-aided cognitive training in patients with neurocognitive vascular impairment: effects on cognition, depression and behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The whole study is observed in males only but the findings suggest the difference in patterns of learning disorder and attentional disorder for model-based RL and model-free RL. The efficacy of a computer-aided cognitive training program is investigated in 85 on depressive symptoms, behavioral symptoms, and cognitive measures in patients having major vascular neurocognitive disorder. The subjects were divided into a control and a treatment group, and all of them received a neuropsychiatric inventory, the Aasberg depression rating scale, the Montgomery, and the mini-mental state examination.…”
Section: Rehabilitation For Neurological Disordersmentioning
confidence: 99%
“…The whole study is observed in males only but the findings suggest the difference in patterns of learning disorder and attentional disorder for model-based RL and model-free RL. The efficacy of a computer-aided cognitive training program is investigated in 85 on depressive symptoms, behavioral symptoms, and cognitive measures in patients having major vascular neurocognitive disorder. The subjects were divided into a control and a treatment group, and all of them received a neuropsychiatric inventory, the Aasberg depression rating scale, the Montgomery, and the mini-mental state examination.…”
Section: Rehabilitation For Neurological Disordersmentioning
confidence: 99%